Lead Generation Authority : Discover A Step-By-Step Plan To Attract More Leads, Close More Sales And Increase ROI In Your Marketing!. - Brock, David (Scribl, 2019)
The best internet marketers and businesses know that the single most important activity they can engage in is building leads. This is the difference between success and failure and it's truer in today's world of online business than it perhaps ever has been. So just what exactly is a lead? Why does it matter so much? And how do you go about building one? Put simply, a lead is someone who mi ...